2021
DOI: 10.1016/j.heliyon.2021.e07449
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, total polyphenol, flavonoid content, in vitro antioxidant and antibacterial activities of Sri Lankan varieties of Murraya koenigii and Micromelum minutum leaves

Abstract: The use of plant materials in traditional medicine as a significant ingredient in synthesizing drugs in the form of decoctions had played a vital role due to their potential therapeutic action. The curry leaves, Murraya koenigii, and Micromelum minutum are two most common aromatic herbs widespread in Sri Lanka and many other Asian countries. They are rich in nutrition and exert several medicinal properties such as antidiabetic, antioxidant, antimicrobial, anti-inflammatory, and anti-carcinogenic due to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 29 publications
0
20
0
2
Order By: Relevance
“…[27] The methanol extract of C. sativum L. had a TFC of 60.87 mg QE/g dry weight, whereas the methanolic extract of M. koenigii had a TFC of 9.75 mg QE/g dry weight, according to D.T. Abeysinghe et al [28] and Hasna Bouhenni et al [29] The flavonoid concentration of leafy vegetables was shown to be considerably influenced by biological, environmental, genetic, seasonal, and yearly fluctuations, according to publications in the literature.…”
Section: Total Flavonoid Content Determination (Tfc)mentioning
confidence: 96%
“…[27] The methanol extract of C. sativum L. had a TFC of 60.87 mg QE/g dry weight, whereas the methanolic extract of M. koenigii had a TFC of 9.75 mg QE/g dry weight, according to D.T. Abeysinghe et al [28] and Hasna Bouhenni et al [29] The flavonoid concentration of leafy vegetables was shown to be considerably influenced by biological, environmental, genetic, seasonal, and yearly fluctuations, according to publications in the literature.…”
Section: Total Flavonoid Content Determination (Tfc)mentioning
confidence: 96%
“…The top three ligands were downloaded in.SDF format from PubChem (https://pubchem. ncbi.nlm.nih.gov/) [8,11,12].…”
Section: Retrieval Of Ligandsmentioning
confidence: 99%
“…Various direct and indirect methods have assessed the antioxidant activities of the plants of the Rutaceae family. Most parts of M. koenigii are reported to be a rich source of plant polyphenols, flavonoids, and alkaloids, possessing a high antioxidant potency [ 98 100 ]. A recent study reported that total antioxidant activity was the highest in M. koenigii (2691 μ mol of ascorbic acid/g sample) among green leafy vegetables [ 101 ].…”
Section: Beneficial Pharmacological Activities Of M Koenigii M Minutum and C Indica mentioning
confidence: 99%